Uji Ketahanan beberapa Varietas Unggul Jagung terhadap Penyakit Gibberella dan Diplodia - Soenartiningsih Soenartiningsih (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Gibberella and Diplodia ear rot is a disease that can damage the corn cobs and corn kernels resulting in lower quality and quantity of seed. The objective of the research are to find the varieties of corn which are resistant the ear rot disease Gibberella and Diplodia. This study was conducted in Limang Karo regency, North Sumatera, a randomized block design with three replications, each treatment comprised 4 rows and each row contained 25 plants with a spacing of 75 x 20 cm. The results showed 25 Hybrid maize tested against Gibberella ear rot there are 7 Hybrid corn hybrids that are resistant to ear rot Kenia-2, NK33, Bima 3, Bima 10 Bima 12 Q, NEI-9008 and X8B649 (check resistance) and moderately resistance there are 9 hybrid that Kenia-3, DK979, NK22, P12, Gumarang, Srikandi putih, Lamuru and Sukmaraga and 9 hybrid to ear rot disease were reacted susceptible and highly susceptible. Whereas from 25 Hybrid maize tested against Diplodia ear rot there are 6 Hybrid corn hybrids resistant to ear rot disease is Kenia - 2, NK33, Bima 3, Bima 12 Q, NEI-9008 and X8B649 (check resistance) while that is moderately resistancet there are 11 hybrid that is Kenia-3, DK979, NK22, P29, Bisi 2, P12, Bima 10, Gumarang, Srikandi putih, Lamuru and Sukmaraga, while 8 hybrid others were reacted susceptible and highly susceptible.